2019
DOI: 10.1109/jphotov.2019.2923337
|View full text |Cite
|
Sign up to set email alerts
|

A Novel TLM Analysis for Solar Cells

Abstract: Despite its widespread usage, the linear regression method used to obtain contact resistivity and sheet resistance from the transmission line model (TLM) can lead to huge errors. The method assumes that contact parameters (both electric and geometric) are identical across the probed structure, such as a solar cell. In contrast, the contact parameters display various processassociated inhomogeneities. This paper analyzes the limitations of the linear fit method by using mathematical analysis and measurements on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…In addition, screen‐printed and dispensed electrodes result in a comparable level of contact resistivity 19,20 . When interpreting the results of contact resistivities, the measurement inaccuracy of the TLM should be kept in mind 51 . Furthermore, it must be pointed out that the manufacturing process and the composition of the ITO layers have a distinct effect on the contact formation of the electrodes to that layer and consequently on the contact resistivity values, as described in the literature 52,53 …”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, screen‐printed and dispensed electrodes result in a comparable level of contact resistivity 19,20 . When interpreting the results of contact resistivities, the measurement inaccuracy of the TLM should be kept in mind 51 . Furthermore, it must be pointed out that the manufacturing process and the composition of the ITO layers have a distinct effect on the contact formation of the electrodes to that layer and consequently on the contact resistivity values, as described in the literature 52,53 …”
Section: Resultsmentioning
confidence: 97%
“…19,20 When interpreting the results of contact resistivities, the measurement inaccuracy of the TLM should be kept in mind. 51 Furthermore, it must be pointed out that the manufacturing process and the composition of the ITO layers have a distinct effect on the contact formation of the electrodes to that layer and consequently on the contact resistivity values, as described in the literature. 52,53 The data allow the following observation: The lateral electrode resistance R lateral predicts if a contact between the Ag electrode and the ITO layer is formed or not.…”
Section: Required Curing Condition For Low-resistivity Contactsmentioning
confidence: 99%
“…The resistivity is understood to be the quantity that characterises the metal–semiconductor junction, considering the area above and below the junction. The value of contact resistance, which depends on the type of paste used, the substrate resistance, and the temperature of the metallisation process, can be determined experimentally—for example, by using the TLM (transmission line model) method [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ] or the PD (potential differences) method [ 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. In the case of the TLM method, the measurement consists of forcing an electric current signal between the selected pair of adjacent front conductive lines on the tested sample through the supply soda and the spontaneous generation of a potential difference in them through the measuring probes ( Figure 1 a).…”
Section: Methods Applied To Measuring Selected Parameters Of the Electrical Properties Of Photovoltaic Cellsmentioning
confidence: 99%
“…However, standard CSM and TLM cannot deliver an accurate extraction of ρ c when it comes to contacts that show Schottky behavior such as HTL/ n ‐Si 74,82 . In addition, by algebraic analysis and experimental verification, Mir et al revealed that certain assumptions of linear regression may cause the ρ c to be seriously overestimated, resulting in inhomogeneities both at wafer level and contact level 83 . Meanwhile, Wang et al proposed an expanded CSM which has generally higher precision confirmed by simulation 74 …”
Section: Dopant‐free Passivating Contacts: Mechanism Characterization...mentioning
confidence: 99%